Peculiarities of Changes of Young Swimmers’ Anthropometric Profile in the Time of Intensive Training and Its Correlation with Sports Results (Baltic Journal of Sport and Health Sciences, 2019)
Background. Knowledge of the peculiarities of anthropometric indicators, body weight components, and somatotype of athletes is important for coaches, sports scientists, and sports physicians at all stages of perennial training, starting with children’s sport. Often this is seen as an important indicator for identifying talented children in sport. The aim of this study was to determine how the anthropometric and body weight profile of young swimmers (11–12 years) significantly changes during the training period, and the correlation of these indicators with the competition results in the chosen event.Methods. The study included 24 young (aged 11.7 ± 0.5 years) national level swimmers – girls (n = 14) and boys (n = 10) with 3 to 4 years of sports experience in the national competitions and demonstrating high results in their age group. We investigated longitudinal anthropometric measurements, body mass components, established the somatotype and handgrip strength. The change of indicators was analysed during the training period of five months as well as its correlation with the result in the chosen sport. Sports results were rated by FINA ranking points.Results. The anthropometric longitudinal and transverse dimensions of girls and boys increased during the study period, however, there was no difference between the sex groups except for the length of the foot (it was higher in the group of boys, p < .05). The analysis of body weight components showed that girls had higher body fat mass and a percentage of body fat than boys (p < .05). The results of boys’ swimming had statistically significant links with their height (r = .857), foot length (r = .805), body weight (r = .857), lean mass and muscle mass (r = .927) and right handgrip strength (.786). There was no significant correlation between these indicators in the group of girls.Conclusion. The results of the study suggest that the characteristics of the anthropometric profile as a prognostic indicator for the viability in the chosen sport for boys were more significant than for girls.